(untitled) (Fiep Bulletin - online, 2014)
Clinical quantitative trial of therapeutic intervention type that aimed to evaluate, "before and after", the effectiveness of non-pharmacological strategies for relieve the pain intensity of women in the active phase of childbirth labor. The study was developed in a public maternity in the city of Natal/RN, in Northeast region of Brazil, and had as a sample, 100 considered low-risk women. To evaluate the pain intensity during childbirth, used the visual analogue scale for measurement. After the application of non-pharmacological strategies (breathing exercises, muscle relaxation and lumbosacral massage), the women of the study felt significant relief (ñ <0.05) in the pain intensity. It follows that these strategies applied in the study’s women were effective in relieving the childbirth pain, in the active phase of childbirth labor, which means in the phases of acceleration, deceleration and maximum slope, being more effective in maximum inclination and deceleration stages. The findings of this study point out to the need for further clinical researches focusing the use of these and other effective non-pharmacological strategies for pain relief in childbirth, aiming humanized actions to mothers’ assistance. Knowing these conclusions, it is expected that the data found in this research would come to contribute in the improvement of obstetrical practice focused on childbirth labor, especially in its active phase, in a way to relief pain of women in the process of childbirth labor. For nursing and to health assistance, it may help on their theoretical development, providing the knowledge expansion about the practice in obstetrical nursing, in addition of contributing to the awareness and consciousness of health professionals involved in the team and in the systematical practice directed to the actual conditions of woman during childbirth labor.